Barriers to Accessing Care (BACE) Score in Patients Attending Mental Health Services - Khanal, Iswori (NPRC Journal of Multidisciplinary Research, 2024)
Background: The World Health Organization’s definition of health has stressed mental health as an important component. Terms such as access, availability, utilization and coverage have often been used interchangeably to reveal whether people are receiving the services, they need. To reduce the unmet need for treatment and it is crucial to identify barriers in mental health to reduce adverse effects associated with the absence or postponement of timely treatment. Methods: A cross-sectional study was performed in Mental Hospital, Lalitpur, Nepal. People suffering from mental illness who fulfilled the inclusion criteria were recruited and BACE scale was administered along with relevant details of participants. Results: Among the patient reported barriers related to stigma, the most reported concern was “ concerned that I might be seen as weak for having a mental health problem “(33.6 %), Among the reported instrumental barriers in BACE scale , “having no one who could help me get professional care (18.2)“ was the most reported major barrier, Among the different attitudinal components in BACE scale “wanting to solve problem on my own” (21.9%) was the most reported barrier. Conclusion: Thus, it can be concluded that people people suffering from mental illness also experience different barriers during help seeking . This barriers is found more on people below 45 years of age and people with low socio economic status. These barriers influence the quality of life in terms of decline in physical health and environment. Novelty: BACE scale administered on large sample size.